DINAMIKA KURIKULUM PONDOK PESANTREN MANBAUL ULUM KECAMATAN KERTAK HANYAR KABUPATEN BANJAR - ., Mudhiah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2009)
For his special position and function, pondok pesantren is the alternative development mode which people centered development and the center of developing value oriented development. As the earlier education system in Indonesia, pondok pesantren had a long history and tradition together with the coming of Islam its self and still surviving until now. It happened for the pondok pesantren not only have the capability in adapting the culture but also for his existential characters. From its supported factors, that is the curriculum. The curriculum is very important in an education building. Its the main component that used to be the reference that determine the teaching substance, directing the teaching mechanism, and the parameter of the succeed and the quality of education result.